The Influence of Intellectual Capital on the Financial Performance of Banks Listed in Bahrain - Almusali, Mahfoudh Abdul Karem Mahfoudh (2009)
This study examines if intellectual capital influences the financial performance of banks listed in Bahrain by using data drawn from 18 banks listed in Bahrain Stock Exchange for a period of three years from 2005 to 2007. Pulic’s Value Added Intellectual Coefficient (VAIC) is used as the efficiency measure of capital employed and intellectual capital. By using correlation and regression analysis, the results support the hypothesis that firms’ intellectual capital has a positive impact on financial performance of banks listed in Bahrain. In addition, when it is classified into major components, it is found that there is a positive relationship between capital employed efficiency (CEE) and human capital efficiency (HCE) and banks` financial performance. On the other hand, empirical findings fail to find any strong association between structural capital efficiency (SCE) and financial performance of the banks listed in Bahrain. In general, empirical findings suggest the efforts to improve intellectual capital base of the banks listed in Bahrain still appear limited. Banks listed in Bahrain still appear to place greater weight on corporate performance based on physical capital assets. A possible policy implication of these findings from this study may be that policy makers may have to adjust or intensify initiatives to encourage greater acceptance and understanding of the concept of intellectual capital, and the development of related assets.